Interdependence of interests of sellers and consumers by selling agricultural products on marketplaces - Kuzman Boris; Prdić Nedeljko; Kostić Sara (Ekonomika Poljoprivrede (1979), 2022)
Marketplace sales in trade dates back to the Middle Ages. The meaningfulness and development of communication gained real meaning with the development of the marketplaces. Today, personal selling is part of the distribution of agricultural products and part of modern marketing. With the development of the global market and modern information technologies, the role of marketplace sales has taken on another dimension. The aim of this paper is to define the model of efficient sales on the market through direct marketing, sales promotion and living words. The results of theoretical research are based on scientific and professional literature, statistical data and tables, authors' experience, whereas field empirical research was conducted using a questionnaire. The results of empirical research show that the average desire for changes in the behaviour of sellers in sales and consumers in shopping is not present enough. From the conducted research, it can be concluded that in certain previously mentioned aspects of changes in behaviour, marketing communication can be established that will contribute to increasing consumer satisfaction and information.